Ethnic Prejudice in Adolescent: The Role of Cultural Intelligence, Intergroup Contact and Ethnocentrism as Mediator - Santi, Dyan Evita; Pratitis, Niken Titi (Universitas Ahmad Dahlan, 2025)
This study aims to examine the effect of cultural intelligence and intergroup contact on ethnic prejudice in adolescents, with ethnocentrism as a mediating variable. The study was conducted on 308 adolescents using a quantitative approach and analyzed using Structural Equation Modelling (SEM) through the JASP program. The results showed that the resulting model had adequate fit (SRMR = 0.070; RMSEA = 0.092; CFI = 0.902; GFI = 0.983). Directly, cultural intelligence had a significant positive effect on ethnic prejudice, while intergroup contact had a significant negative effect on ethnic prejudice. Ethnocentrism also showed a strong positive effect on ethnic prejudice. The analysis of the mediation effect revealed that mediating ethnocentrism significantly affected cultural intelligence and intergroup contact on ethnic prejudice. These findings suggests that an increase in cultural intelligence or frequency of contact does not necessarily decrease ethnic prejudice without decrease in the level of ethnocentrism. Theoretical and practical implications are discussed in the context of developing interventions to reduce ethnic prejudice among adolescents.